Modes of hardening of a high-strength (α+β)-titanium alloy VT23 for use in aeronautical engineering - V. N. Fedulov (Литьë и металлургия, 2018)
New modes of thermal hardening of various semi-finished products made from high-strength titanium alloy VT23 are recommended, and the mechanical and special properties obtained as a result of their research are given.